How Do Vulnerable People in Bangladesh Experience Environmental Stress From Sedimentation in the Haor Wetlands? An Exploratory Study. Issue 7 (8th July 2022) - Islam, Mohammad Nazrul; Atiqul Haq, Shah Md; Ahmed, Khandaker Jafor; Best, Jim
Abstract: The haor landscape is a wetland ecosystem in northeast Bangladesh, comprising shallow depressions that undergo large changes in water inundation between the monsoon and dry seasons. Sediment is supplied to the haor from rivers originating in the adjacent Shillong Plateau, and can adversely affect these largely arable agricultural lands. The critical adverse effects of changing hydrology and enhanced sedimentation due to anthropogenic change include the reduction of natural water storage capacity, changes in the timing and magnitude of floods, and increasing loss and damage to crops, which consequently affect the livelihoods of wetland dwellers. This study employs a mixed‐methods approach to investigate how sedimentation has affected the livelihoods of the residents and the pressures they experience. Cross‐sectional surveys and interviews were conducted with 180 respondents in Lubar and Pochashul Haors (LPH), Sunamganj District, and allied with an analysis of satellite images that reveals the nature of landscape change over the past 56 years. Our findings confirm that sedimentation has been promoted through both natural processes of alluvial fan progradation and anthropogenic forcings. Enhanced sedimentation threatens the agriculture of the region and affects the livelihood of local inhabitants, leading to other societal issues related to income, education, employment, health, displacement, and sexual harassment. The mixed methods employed herein are essential tools to reveal these effects. In order to reduce the vulnerability of the local population, a transboundary dialog between India and Bangladesh is needed to realize measures to protect wetland resources and achieve progress towards environmental sustainability. Key Points: Sedimentation has fostered a new pattern of local disasters in wetland areas Both natural and anthropogenic factors cause accelerated sedimentation Enhanced sedimentation can lead to societal issues related to income, education, employment, health, displacement, and sexual harassment